Bibliotherapy as a Non-pharmaceutical Intervention to Enhance Mental Health in Response to the COVID-19 Pandemic: A Mixed-Methods Systematic Review and Bioethical Meta-Analysis - Monroy-Fraustro, Daniela; Maldonado-Castellanos, Isaac; Aboites-Molina, Mónica; Rodríguez, Susana; Sueiras, Perla; Altamirano-Bustamante, Nelly F.; de Hoyos-Bermea, Adalberto; Altamirano-Bustamante, Myriam M. (Frontiers in Public Health, 2021)
Background: A non-pharmaceutical treatment offered as psychological support is bibliotherapy, which can be described as the process of reading, reflecting, and discussing literature to further a cognitive shift. The coronavirus disease 2019 (COVID-19) pandemic demands a response to prevent a peak in the prevalence of mental health problems and to avoid the collapse of mental health services, which are scarce and inaccessible due to the pandemic. Thus, this study aimed to review articles on the effectiveness of bibliotherapy on different mental health problems. Methods: A systematic review was conducted to examine relevant studies that assess the effectiveness of bibliotherapy in different clinical settings as a treatment capable of enhancing a sense of purpose and its surrounding values. To achieve this, a systematic review, including a bioethical meta-analysis, was performed. A variant of the PICO (Participants, Intervention, Comparison, and Outcome) model was used for the search strategy, and the systematic review was conducted in three databases: PubMed, Bireme, and OVID. Inclusion criteria were relevant studies that included the keywords, excluding documents with irrelevant topics, studies on subjects 15 years or younger, and in languages besides Spanish or English. Starting with 707 studies, after three rounds of different quality criteria, 13 articles were selected for analysis, including a hermeneutic analysis, which was followed by a fourth and final recovery round assessing bibliotherapy articles concerning healthcare workers. Results: Our findings showed that through bibliotherapy, patients developed several capacities, including the re-signification of their own activities through a new outlook of their moral horizon. There are no research road maps serving as guides to conduct research on the use of bibliotherapy to enhance mental health. Additionally, values such as autonomy and justice were closely linked with positive results in bibliotherapy. This implies that bibliotherapy has the potential to have a positive impact in different settings. Conclusions: Our contribution is to offer a road map that presents state-of-the-art bibliotherapy research, which will assist institutions and healthcare professionals to plan clinical and specific interventions with positive outcomes.